Modern weapons and military equipment for issue 3/2014 - Ostojić, Nikola M. (Vojnotehnički glasnik / Military Technical Courier, 2014)
A new generation of military protective masks Hybrid kvadrotori at AUVSI 2014 New equipment driver in the convoys of the combat zone Russian systems for electronic warfare